Effectiveness of Chromebooks in Learning Indonesian Language: A Literature Review - Siti Suwadah Rimang; Luli Muliana; Andi Dewi Aulia; Nur Alam Syah; Syamsiah B (Universitas Muhammadiyah Enrekang, 2025)
This study is a systematic study that aims to evaluate the effectiveness of using Chromebooks in learning Indonesian, especially in the context of primary and secondary education in Indonesia. This study also explains the socio-political dynamics related to alleged corruption in the procurement of educational technology devices, which can affect the implementation and learning outcomes. Using the Systematic Literature Review (SLR) method, this study analyzes and analyzes relevant scientific literature from 2015–2025. The results of the study indicate that although Chromebooks have the potential to increase student engagement and learning quality, there are systematic challenges such as limited teacher training, uneven infrastructure, and lack of transparency in procurement policies that can hinder learning effectiveness.